O uso de textos de divulgação científica em aulas de genética na educação básica - Santos, Elizandra Paulino dos (2018)
The questioning about the fundamental role of the School in contemporary society is recurrent by the professionals of Education faced with the difficulties of constructing models and teaching practices that cover the real needs of the students. Considering that the purpose of the School is to form critical and reflective citizens able to play their roles in society consciously, full mastery of reading ability is an essential condition. Therefore, we use in this work texts of scientific dissemination (SDT) as didactic resource due to its great pedagogical potential. The research had as objectives: to elaborate and to apply a didactic sequence with theoretical contents of genetics in a STS perspective; identify the STS approach of the study; to evaluate how the reading of SDT contributed to the development of the reading ability; to evaluate if the use of SDT as didactic resource contributed to the consolidation of the learning of concepts of Genetics. As an instrument of data collection, a questionnaire of open answers and questions of interpretation of texts were used. The didactic sequence was elaborated with texts extracted from the Magazines Ciência Hoje and Pesquisa FAPESP. Its application was made in 2016, in a class of the 2nd year of the high school of a public school in the interior of São Paulo. The analysis of the answers given by the students to the questions of interpretation of the SDT revealed difficulties in making inferences and in recognizing the overall aspect of the texts. Regarding the levels in the cognitive domain of the revised Bloom taxonomy, it was expected that students in the second year of high school were able to perform activities belonging to the categories remember, understand, analyze and evaluate, but the results indicate that the correct answers to questions are when they require only the recognition of explicit information (category remember). As for learning in genetics, we perceive a better mastery of concepts such as gene, genome, chromosomal mutation, DNA and transgenics. The small progress in learning conquered leads us to believe that SDT is an important instrument for the integration between Science, Technology and Society (STS) and that its use in Science classes will allow an introduction of a STS education system.